Strategi E-Commerce Sebagai Fokus Untuk Tujuan Dalam Pengumpulan, Penganalisaan, Dan Manajemen Kesuksesan Terhadap Informasi Bisnis - Yulianto, Yulianto (AMIK Jakarta Teknologi Cipta Semarang, 2006)
E-Commerce of none merely selling online, this is any type business conducted by online. What your business is consumer-oriented and business to business and what nonchalant is its target (sale, information, distribution, manufacture, education, or the entertainment amusement). Principal though e-commerce have giant budget, which can be successful applied in small business problem, but just remain to be of small business have unique issue by self. Small business cope to its staff remain to a little until know the way of to make goals and draw correct visitor. Some people assume e-commerce have to do a dozen staff, have to think a lot of stratagem, develop; building database relational, and pay for small business gratuity is owned to access internet, but by e-commerce, and the opportunity online existence, hence will be created by an focus to become tuition to form strategy focusing as key in successfulness management for the big small industry till Keyword: e-commerce, branding, broad market.